AKTUALISASI NILAI-NILAI KONSTITUSI DALAM KEBIJAKAN PERDAGANGAN INDONESIA DI TINGKAT REGIONAL DAN MULTILATERAL - Dias Satria; Farah Wulandari (Journal of Indonesian Applied Economics, 2011)
The purposes of this study were to analyze the implementation of the Indonesian con-stitutional  values  in  Indonesia  and  in  the  regional  level of  trade policies  (AFTA-ASEAN Free Trade Area). The method used is a qualitative approach. The findings ofthis research stated that there are some trade policy that misses thebasic values  of the1945 Constitution and Pancasila, resulting inmismanagement in development policyand therefore contributesto lowering the level of public welfare in general. The policy,among others, is the policy of trade protection is not based on the principle of wealthcreation and equitable distribution, but is based on the behavior of crony-capitalism;government policiesrelated to foreign ownership in an investment is still not heedingthevalues  and principles of broad benefit of welfare, justice andequity; and governmentprotection policies in the agriculturalsector is still not optimal to create a high com-petitiveness.Keywords: constitution, international trade, welfare and equity.